Making Research Results Relevant and Useable: Presenting Complex Organizational Context Data to Nonresearch Stakeholders in the Nursing Home Setting. Issue 4 (21st April 2016) - Estabrooks, Carole A.; Knopp‐Sihota, Jennifer A.; Cummings, Greta G.; Norton, Peter G.
ABSTRACT: Background: The success of evidence‐based practice depends on clearly and effectively communicating often complex data to stakeholders. In our program of research, Translating Research in Elder Care (TREC), we focus on improving the quality and safety of care delivered to nursing home residents in western Canada. More specifically, we investigate associations among organizational context, the use of best practices and resident outcomes. Our data are complex and we have been challenged with presenting these data in a way that is not only intuitive, but also useful for our stakeholders. Aim: To illustrate a technique of organizing and presenting complex data to nonresearch stakeholders. Methods: Using observational data previously collected within the TREC study, we used k‐means cluster analysis to categorize nursing home resident care units or facilities within our sample into two distinct groups—those with more favorable contexts (work environment) and those with less favorable contexts. We then produced scatter plots to illustrate group differences between context and various quality indicators among resident care units or facilities. Results: Care aides working on units with more favorable context reported higher use of best practices. When aggregated at the nursing home facility level, facilities with low rates of both urinary tract infections and indwelling catheter use are higher in organizational context. When feeding back these results to stakeholders, we identify their units so that they are able to visually assess their units, both relative to each other and relative to all other units and facilities both within and among provinces. Linking Evidence to Action: Although we have not formally evaluated this method, we have used it extensively as part of the feedback we provide to stakeholders. As we are examining modifiable aspects of context, the stakeholder can then identify areas for improvement and thus implement a focused plan.